Do Students' Perceptions of Unsafe Schools and Experiences With Bullying Hinder the Effects of Family and School Social Capital in Deterring Violence?. (October 2018) - Radu, Monica Bixby
Prior research establishes that capital investments from both families and schools are imperative for youths' socialization and development. Yet current research neglects to test if negative perceptions and negative experiences during adolescence may hinder the effectiveness of family and school capital on adolescent and young adult behavioral outcomes. Drawing from ecological systems theory and social capital theory, I examine the influence of youths' perceptions of schools' safety, bully victimization, and family and school social capital predicting violence. I use data from multiple waves from the National Longitudinal Survey of Youth (1997) ( N = 4, 130). I find that the bonds between youths and their families and youths and their schools are important agents of social control. However, my findings suggest that being the victim of bullying may influence the process through which bonds to conventional institutions help prevent problem behaviors. This suggests that a theoretical approach that considers investments in youths from multiple contexts and youths' experiences with victimization may be better suited for predicting adolescent and young adult violence.